PENGARUH PEMBERIAN MINUMAN JAHE MERAH TERHADAP INTENSITAS NYERI HAID PADA REMAJA PUTRI - Ela Rohaeni; Iis; Tiktik Sartika (Rena Cipta Mandiri, 2025)
Menstrual pain is a gynecological complaint due to an imbalance of the hormone progesterone in the blood, resulting in the most common pain in women. Women who experience menstrual pain produce 10 times more prostaglandins than women who do not experience menstrual pain. The purpose of this study was to determine the effect of giving red ginger drinks on the intensity of menstrual pain in adolescent girls at the Cikelet Health Center, Garut Regency in 2024. This study used an experimental analytical research design of the pre-experimental type with a pretest - posttest one group design approach. The population in this study were all adolescent girls in grades 10 and 11 aged 16 to 19 years at the Cikelet Health Center, Garut Regency and the sampling technique used in this study was the total sampling technique. Data analysis used univariate and bivariate. The results of the study showed the intensity of menstrual pain in adolescent girls before being given red ginger drinks at the Cikelet Health Center, Garut Regency in 2024. Most of the 20 people (66.7%) experienced moderate pain, after being given red ginger drinks, most of the 16 adolescent girls (53.3%) experienced mild pain, the results of the Paired Samples Test with a significance level of α = 0.05 obtained the result of p = 0.001 which means p <0.05, namely Ha is accepted, which means there is an effect of giving red ginger drinks on the intensity of menstrual pain in adolescent girls at the Cikelet Health Center, Garut Regency in 2024. The results of this study are expected to increase knowledge and insight in midwifery, especially the effect of giving red ginger on reducing menstrual pain in adolescent girls.